Microstructural and Residuals Stress Analysis of Friction Stir Welding of X80 Pipeline Steel Plates Using Magnetic Barkhausen Noise - Avila, J. A. [UNESP]; Conde, F. F.; Pinto, H. C.; Rodriguez, J.; Grijalba, F. A.F. (Springer Nature, 2019)
Friction stir welding is a solid-state joining method conducted under large stress and strain conditions at low peak temperatures when compared to arc welding. Friction stir welding produces a large variety of microstructures and a M-shaped residual stress line profile along the cross-section of the welds. In this work, we present the use of magnetic Barkhausen noise to qualitatively assess the residual stress profile along the transverse direction of a two-pass friction stir welding butt joint on a X80 pipeline steel. Results were compared and correlated to X-ray diffraction, microstructural and hardness characterization. The peak position and the root mean square profiles of the magnetic Barkhausen noise reproduced the residual stress profile obtained by X-ray diffraction and the hardness profile, respectively. These results can be used for developing a qualitative quality control method for friction stir welding joints in other steels.
Keywords: Friction stir welding; Magnetic Barkhausen noise; Residual stress; X-ray diffraction; X80 pipeline steel